Resistensi Masyarakat Terhadap Kebijakan Pembangunan RISHA di Desa Bayan, Lombok, NTB - Anggun Kinanti, Sarita; Suwena, I Wayan; Sudiarna, I Gusti Putu (Sunari Penjor : Journal of Anthropology; Vol 3 No 1 (2019)DO - 10.24843/SP.2019.v3.i01.p02, 2021)
The Ministry of Public Works and the Public Housing (PUPR) has proposed innovations named Rumah Instan Sederhana Sehat (RISHA) as a form of post-disaster rehabilitation and reconstruction in Lombok, West Nusa Tenggara in 2018. One of the villages that received the innovations was Bayan village. Bayan community does not accept RISHA to be built as their new residence. This research focuses on two problems: (1) Why the Bayan people performs resistance to RISHA and (2) how the form of the resistance of Bayan people to RISHA. This research aims to study the determinants and the forms of resistance that the Bayan people has committed to the RISHA. The study was conducted for two months using qualitative research methods implementing the model of ethnographic research. The ethnography itself includes observation techniques, interviews, and library studies. The supporting instruments of this research are interview guidelines, voice recording equipment, cameras, and stationery. Based on the results of the research, it is known that the determinant that causes the Bayan people commit to RISHA is indigenous belief and framing made by the Government connected to the politic elections in 2019. The form of resistance performed by Bayan people are doing traditional deliberations, destruction of modern elements in the ancient Mosque of Bayan Beleq, efforts to build their own homes, dodge and do not want to know, as well as looking for alternative houses other than RISHA.